IFN-β Deficiency Results in Fatal or Demyelinating Disease in C57BL/6 Mice Infected With Theiler’s Murine Encephalomyelitis Viruses - Bühler, Melanie; Runft, Sandra; Li, Dandan; Götting, Jasper; Detje, Claudia N.; Nippold, Vanessa; Stoff, Melanie; Beineke, Andreas; Schulz, Thomas; Kalinke, Ulrich; Baumgärtner, Wolfgang; Gerhauser, Ingo (Frontiers in Immunology, 2022)
Type I Interferons (IFN-I) are important inducers of the antiviral immune response and immune modulators. IFN-β is the most highly expressed IFN-I in the central nervous system (CNS). The infection of SJL mice with the BeAn or the DA strain of Theiler’s murine encephalomyelitis virus (TMEV) results in a progressive demyelinating disease. C57BL/6 mice are usually resistant to TMEV-induced demyelination and eliminate these strains from the CNS within several weeks. Using C57BL/6 IFN-β knockout (IFN-β-/-) mice infected with TMEV, we evaluated the role of IFN-β in neuroinfection. Despite the resistance of C57BL/6 wild type (WT) mice to TMEV infection, DA-infected IFN β-/- mice had to be killed at 7 to 8 days post infection (dpi) due to severe clinical disease. In contrast, BeAn-infected IFN-β-/- mice survived until 98 dpi. Nevertheless at 14 dpi, BeAn-infected IFN β /- mice showed a stronger encephalitis and astrogliosis, higher viral load as well as higher mRNA levels of Isg15, Eif2ak2 (PKR), Tnfa, Il1b, Il10, Il12 and Ifng in the cerebrum than BeAn-infected WT mice. Moreover, the majority of IFN β-/- mice did not clear the virus from the CNS and developed mild demyelination in the spinal cord at 98 dpi, whereas virus and lesions were absent in the spinal cord of WT mice. Persistently infected IFN β-/- mice also had higher Isg15, Eif2ak1, Tnfa, Il1a, Il1b and Ifng mRNA levels in the spinal cord at 98 dpi than their virus-negative counterparts indicating an activation of IFN-I signaling and ongoing inflammation. Most importantly, BeAn-infected NesCre+/- IFN βfl/fl mice, which do not express IFN β in neurons, astrocytes and oligodendrocytes, only developed mild brain lesions similar to WT mice. Consequently, IFN-β produced by neuroectodermal cells does not seem to play a critical role in the resistance of C57BL/6 mice against fatal and demyelinating disease induced by TMEV strains.